Perlindungan Anak di Lembaga Daycare: Analisis Kasus Kekerasan pada Daycare Little Aresha Yogyakarta - Nadhira Saufa Aliqa; Salwa Aisyabila Alqirana; Citra Mita Sari Banjarnahor; Junita Friska (Jurnal Keluarga Sehat Sejahtera, 2026)
The alleged case of child abuse at Daycare Little Aresha Yogyakarta has become a concerning issue and shows that childcare institutions have not yet fully become safe spaces for children. This study aims to analyze the case through the perspectives of child protection, victimology, institutional supervision, and the legal responsibility of daycare management. The method used is a literature study by reviewing scientific journals as supporting sources for analysis and using news reports as case data. The focus of this study includes child protection, the impact of violence on children, weak institutional supervision, and the importance of caregiver capacity in implementing child-friendly care. The findings show that violence in daycare can affect children’s physical, psychological, and social conditions. In addition, the imbalance of power relations between caregivers and children, weak licensing systems, and lack of supervision are factors that increase the risk of violence. Therefore, improving caregiver capacity, strengthening regulations, conducting regular supervision, and ensuring victim recovery are important steps in creating a safe, professional daycare environment that supports children’s optimal growth and development.